Flotsam - Erich Maria Remarque (New York Random House Trade Paperbacks, 2013)
From the beloved author of All Quiet on the Western Front, Flotsam is a terrifying portrait of Europe as the Nazi shadow falls over the continent. Political dissidents, Jews, medical students, petty criminals: Among the thousands of displaced persons traveling the unpaved roads of Europe, there are Steiner and Kern. Both have irritated officials for outstaying their two-week sojourn in Czechoslovakia. And so they must leave. Not that either has any place to go. Not in 1939. But when a man is led by a guard to the border of one country, he must try another. Until he is escorted from that one too. Living hand-to-mouth, selling shoelaces and safety pins for a few pennies, Steiner and Kern find that, remarkably, there are still pleasures to be had. Paris, for one; love, for another. For amid the heartless cruelty and cold-blooded laws of the Nazi state, there is still humanity and kindness. And there is incomparable joy in falling in love, surviving, and telling your story so it is never forgotten.
Keywords: Classics; Historical fiction; Fiction; War fiction